Perceptions of Parents And Teachers on Students With Learning Disabilities (SLD) In Malaysia - Rohaizat Ibrahim; Kway Eng Hock; Ciptro Handrianto; M Arinal Rahman; Januard Dagdag (International Journal of Education, Information Technology, and Others, 2021)
This paper reports on a survey of perception parents and teachers on student with learning disabilities (SLD) in Malaysia. The participants for this study consisted of 336 parents of SLD and 248 teachers who teach SLD in Selangor. The results showed that parents and teachers agreed that students of SLD had still low self-esteem and they did not have accurate and enough information for their educational progress. The paper concludes that further program to assist the special education program in Malaysia is required to address these shortcomings, and that, the use of ICT may be the solution for the better treatment of SLD in Malaysia. Collaboration among parents, teachers, and the government is needed to develop this program to improve special education in Malaysia.